PENERAPAN METODE JIT PEMBELIAN BAHAN BAKU DALAM MENINGKATKAN EFISIENSI BIAYA BAHAN BAKU - Diaz, Adriany Pratiwi; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out and to analyze the implementation of Just in Time method on PT. Semanggimas Sejahtera Surabaya to increase the efficiency of raw materials. The research has been carried out by using qualitative method whereas the analysis data has been done by using descriptive analysis. The qualitative approach is carried out by the researcher because the researcher is not proofing a hypothesis; on the other hand the researcher is comparing and analyzing the implementation of raw materials inventory by using traditional method and Just in Time method (JIT). The result of the research shows that before 2014 the company still runs the inventory purchasing system by using traditional method. Meanwhile, start from 2014 the company has implemented the Just in Time (JIT) in order to conduct the reduction of inventory cost. By using Just in Time system the booking fee and the storage cost is more efficient when it is considered from the booking fee 3.98% and the storage cost 1.94%, the total efficiency is 5.92%. Based on the result of the discussion it can be concluded that in order to enhance the efficiency of raw materials inventory cost, the company should maintain the Just in Time method and the company should establish information network with the suppliers.Keywords: JIT Purchasing, the Cost of Purchasing, Storage Cost